Risk Analysis of Disaster Management Project in Central Sulawesi Province - Andi Rizal; T. Hilmansyah; M. Amin; Muhammad Sutrisno (Universitas Muhammadiyah Palu, 2024)
Risk is the cause of unexpected conditions that can cause loss, damage, or loss. This is due to the risks contained in construction projects that can affect the productivity and quality of the project. The Central Sulawesi Province 2 School Infrastructure Disaster Management Project, located in Sigi Regency, Central Sulawesi Province, is a project that handles the construction of school infrastructure. This project is also not free from risks that can cause the project not to run as planned and suffer losses. Based on the description above, the researcher is interested in conducting a risk analysis that occurs in the Central Sulawesi Province School Infrastructure Disaster Management Project 2. The methods used in this study are data collection by distributing questionnaires, conducting data analysis, descriptive statistics, reliability tests, risk analysis, risk response and risk control. This research was carried out for 6 months, starting from preparation, implementation, data collection, and monitoring and evaluation. The outputs to be achieved in this study are scientific articles published in research journals and reports on the results of activities.